Dating in the time of "relational filter bubbles": exploring imaginaries, perceptions and tactics of Italian dating app users. Issue 1 (2nd January 2020) - Parisi, Lorenza; Comunello, Francesca
ABSTRACT: In this paper, we address algorithmic imaginary, perception and tactics of Italian dating apps users. Little attention has hitherto been devoted to the ways in which the algorithms employed by mobile dating platforms (to rate users, to manage user visibility, to arrange results) might contrast, or enhance, people's homophily . Our goal is to explore whether and how mobile dating algorithms modify the perception of what we define as "relational filter bubbles"; and whether, and how, users believe dating algorithms reshape (extend or limit) the heterogeneity of their intimate interactions. The paper builds on literature addressing online dating, the datafication of society, the rise of the so-called quantified self, and of the algorithmic culture. We organized 4 focus groups involving Italian dating apps users, who reported a variety of sexual orientations and of dating apps usage. Overall, while dating apps' algorithms operate in an opaque way, participants developed an "algorithmic imaginary". Moreover, they appreciate the role of mobile dating apps in reinforcing their relational homophily (their tendency to like people that are "similar" to them), whilst, at the same time, mainly using these apps for increasing the diversity of their intimate interactions in terms of extending their preexisting networks.